Addition of palm oil in diet of dairy ewes reduces saturates fatty acid and increases unsaturated fatty acids in milk - Bianchi A.E. (2018)
© 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Sheep milk production is becoming an important alternative in the agricultural sector. It is used principally to produce fine cheeses, yogurts, and ice creams, and these produced from sheep's milk are beneficial to human health. Previous study with palm oil shows increase in fat levels in sheep's milk. Our hypothesis for increased fat in milk is that palm oil increases lipid metabolism as well as tissue reserves. Sheep consuming this palm oil will have a change in the fatty acid profile of milk, increasing levels of unsaturated fatty acids. Therefore, the aim of this study was to determine the levels of cholesterol and triglycerides, as well as fatty acid profile of milk these ewes fed of palm oil. Materials, Methods & Results: Thirty-six lactating sheep were divided in four groups (n = 9), with each group receiving various concentrations of palm oil in diet (0%, 2%, 4%, and 6% which corresponds to T 0, 2, 4 and 6, respectively). The diets in each treatment were isoproteic and isoenergetic. The experiment lasted 120 days, and blood and milk samples were collected on days 60 and 12 of the experiment. Blood was collected for seric analysis of lipid metabolism. Was collected milk samples and analyzed the content of saturated fatty acids (SFAs), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA). An increase (P < 0.05) in triglyceride and coleterol levels in the serum of the animals that received the highest concentrations of palm oil in the diet (T4 and T6). The centesimal composition of fat, lactose, and protein in milk was not different at days 60 and 120 (P > 0.05) between groups, but numerically the animals in T4 and T6 had higher percentage of fat in milk. A decrease in milk SFA levels was observed on day 120 at T6. There was a significant reduction in caproic acid, caprylic acid, hendecanoic acid, lauric acid, and pentadecyl acid. The levels of palmitic acid (C16:0) increased when compared with the control group. Also at 150 days, it was observed a reduction in the percentage of area capric acid and myristic acid in animals that had higher doses of calcium salts in the diet, different from stearic acid, which increased. A variability in MUFA levels was observed during the evaluated periods, i.e. heptadecenoic acid decreased on days 60 and 120 for animals of T6; an increased content of elaidic acid was observed on day 60, and levels of vaccenic acid decreased on day 120 at 6% palm oil. A decrease in PUFA levels was observed on day 60 at T6, specifically a significant reduction in alpha-linolenic and arachidonic acid, as well as levels of conjugated linoleic acid 1 decreased on day 120 for animals supplemented with 6% of palm oil. Discussion: The addition of plama oil in the diet of dairy sheep increased seric levels of triglycerides and cholesterol, as well as positively altered the composition of fatty acids in milk, making a product healthier to the consumer. This study showed that the addition of 2% and 4% palm oil in the feed of dairy sheep promoted a decrease in several SFAs associated with coronoary heart disease after 60 days of treatment. On the other hand, the addition of 6% palm oil promoted an increase of total SFA levels after 60 days of treatment, while decreaseing total PUFA levels. This can be considered harmful to consumers, since several SFA are associated with coronary heart diseases, and several PUFA are linked with reductions in inflammation, stroke, oxidative stress and hepatic disorders. In summary, the consumption of sheep milk who received the diets with 2% and 4% of palm oil can exert beneficial effects for consumers, and may be an option for farmers to increase the milk yield of sheep, and to reduce the profile of saturated fatty acids in milk.